FORMULASI FLAKES PATI GARUT DAN TEPUNG IKAN LELE DUMBO (Clarias gariepinus) SEBAGAI PANGAN KAYA ENERGI PROTEIN DAN MINERAL UNTUK LANSIA - Firda Amalia; Clara Meliyanti Kusharto (Jurnal Gizi dan Pangan, 2013)
The objective of this study was to produce arrowroot starch flakes with dumbo catfish (Clarias gariepinus) flour, as a rich energy, protein, and mineral food for elderly. Design of this study was complete randomized design with four formulas and each combination was replicated two times. A selected formula was determined based on semi trained panelists preference. Acceptance of selected flakes formula was examined by elderly using hedonic test. Flakes by addition of 33.00% of dumbo catfish flour was the selected formula. The chemical properties for selected flakes were as follows 4.00% of water, 4.84% ash, 16.90% protein, 5.21% fat, 69.06% carbohydrate, 14.48% calcium, and 8.61% phosphor. The selected flakes contain 391 kcals energy per 100 g. The selected flakes had contributed more than 20.00% of energy, protein, calcium, and phosphor for elderly people so it can be claimed as a food product rich in energy, protein and minerals.